2000
DOI: 10.1523/jneurosci.20-21-07972.2000
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Endocytosis of GABAAReceptors by an Association with the Adaptin AP2 Complex Modulates Inhibitory Synaptic Currents in Hippocampal Neurons

Abstract: Type A GABA receptors (GABA A ) mediate the majority of fast synaptic inhibition in the brain and are believed to be predominantly composed of ␣, ␤, and ␥ subunits. Although changes in cell surface GABA A receptor number have been postulated to be of importance in modulating inhibitory synaptic transmission, little is currently known on the mechanism used by neurons to modify surface receptor levels at inhibitory synapses. To address this issue, we have studied the cell surface expression and maintenance of GA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
288
1
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 292 publications
(306 citation statements)
references
References 37 publications
16
288
1
1
Order By: Relevance
“…Similarly, N-methyl-D-Aspartate (NMDA) glutamate receptors, which are thought to be functionally impaired in psychosis [84][85] , are endocytosed by clathrin-dependent mechanisms 70 . Other receptors that are implicated in schizophrenia such as AMPA [86][87] and GABA(A) [88][89] are also regulated by clathrin-dependent mechanisms.…”
Section: Altered Cme May Contribute To Synaptic Pathologymentioning
confidence: 99%
“…Similarly, N-methyl-D-Aspartate (NMDA) glutamate receptors, which are thought to be functionally impaired in psychosis [84][85] , are endocytosed by clathrin-dependent mechanisms 70 . Other receptors that are implicated in schizophrenia such as AMPA [86][87] and GABA(A) [88][89] are also regulated by clathrin-dependent mechanisms.…”
Section: Altered Cme May Contribute To Synaptic Pathologymentioning
confidence: 99%
“…P4 blocks the binding of dynamin 1 to amphiphysin and prevents the recruitment of dynamin 1 to the endocytic complex. Biochemical assays showed that this peptide is highly specific and binds with high affinity to a unique site in the dynamin-proline rich domain (Grabs et al 1997;Kittler et al 2000). Treated neurons were then stimulated and used for subcellular fractionation or FM1-43 imaging as described below.…”
Section: Dynamin 1 Inhibitor Treatmentmentioning
confidence: 99%
“…To obtain more direct evidence of the role of dynamin 1 in the altered synaptic vesicle endocytosis in Aβ-treated neurons, we examined whether inhibition of dynamin 1 would cause a similar membranous build-up of amphiphysinin in cultured hippocampal neurons. To inhibit dynamin 1 activity, we used a dynamin 1 inhibitory peptide (P4) which blocks the binding of dynamin 1 to amphiphysin and prevents the recruitment of dynamin 1 to the endocytic complex (Grabs et al 1997;Kittler et al 2000). When these neurons were treated with 50 μM P4 for 30 minutes prior to stimulation they did not show any change in the amphiphysin membrane-to-cytosol ratio when compared to untreated stimulated neurons (Fig.…”
Section: Inhibition Of Dynamin 1 Caused Accumulation Of Amphiphysin Amentioning
confidence: 99%
“…It is evident that GABA A Rs are not static entities in neuronal plasma membranes but undergo rapid movement into and out of these structures (3). Modifications of GABA A R cell surface number underlie changes in inhibitory postsynaptic current amplitude, providing an effective mechanism for regulating the efficacy of synaptic inhibition (3)(4)(5)(6)(7)(8)(9)(10). Under basal conditions, synaptic GABA A Rs are undergoing clathrin-dependent endocytosis (8,10,11).…”
mentioning
confidence: 99%
“…Modifications of GABA A R cell surface number underlie changes in inhibitory postsynaptic current amplitude, providing an effective mechanism for regulating the efficacy of synaptic inhibition (3)(4)(5)(6)(7)(8)(9)(10). Under basal conditions, synaptic GABA A Rs are undergoing clathrin-dependent endocytosis (8,10,11). Given this constitutive endocytosis, the cellular fate of internalized GABA A receptors is critical as their recycling or degradation will affect the number of receptors on the cell surface, and hence the efficacy of synaptic inhibition.…”
mentioning
confidence: 99%